2007
DOI: 10.1111/j.1444-2906.2007.01302.x
|View full text |Cite
|
Sign up to set email alerts
|

Dietary medicinal herbs improve growth and some non-specific immunity of red sea bream Pagrus major

Abstract: The effects of dietary medicinal herbs on growth and some non-specific immunity were investigated in juvenile red sea bream Pagrus major. The fish (mean body weight 24.0 Ϯ 0.2 g) were fed fishmeal diets supplemented with either Massa medicata (Mm), Crataegi fructus (Cf), Artemisia capillaries (Ac), Cnidium officinale (Co), or a mixture of all the herbs (HM), and a control diet without medicinal herbs, for 12 weeks. Survival, specific growth rate, feed efficiency, condition factor and hemoglobin levels were hig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
65
1
2

Year Published

2008
2008
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 92 publications
(80 citation statements)
references
References 19 publications
7
65
1
2
Order By: Relevance
“…One of the components of ImmuPlus, Amlaki, is rich in vitamin C. Dietary administration of small quantities of vitamin C is known to improve fish growth (Shobana, 1997;Misra et al, 2007;Tiwary and Patra, 2008). Ji et al (2007) observed improved growth in Pagrus major fed medicinal herbs.…”
Section: Discussionmentioning
confidence: 88%
See 2 more Smart Citations
“…One of the components of ImmuPlus, Amlaki, is rich in vitamin C. Dietary administration of small quantities of vitamin C is known to improve fish growth (Shobana, 1997;Misra et al, 2007;Tiwary and Patra, 2008). Ji et al (2007) observed improved growth in Pagrus major fed medicinal herbs.…”
Section: Discussionmentioning
confidence: 88%
“…Jaya Kumari et al (2007) have reported enhanced immunity in rohu fed ImmuPlus at various life stages. Investigations with a few plant derived immunostimulants show their immune modulating potential in different fish species when administered through diet (Rao et al, 2006;Christybapita et al, 2007;Divyagnaneswari et al, 2007;Ji et al, 2007;Sahu et al, 2007;Pratheepa et al, 2010). Finn and Nielson (1971) opined that the inflammatory response is greatly influenced by temperature.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…(Jeney et al, 2009;Gabor et al, 2010;Chakraborty and Hancz, 2011;Harikrishnan et al, 2011 (Sivaram et al, 2004;Ji et al, 2007a;Punitha et al, 2008;Talpur, 2014).…”
Section: 서 론mentioning
confidence: 99%
“…V. anguillarum (Ji et al, 2007a). Massa medicate fermentata, Crataegi fructus, Artemisia capillaries, Cnidium officinale 2:2:1:1 0% ( ), 0.1%, 0.3%, 0.5% 1.0% 8 0.3%, 0.5% 1.0% 0.1% (Ji et al, 2007b , , (Seo et al, 2009a).…”
mentioning
confidence: 99%